A nemzetközi szerződések kihirdetéséről aggályok, dilemmák - Bodnár László (Szegedi Tudományegyetem Állam- és Jogtudományi Karának tudományos bizottsága Szeged, 2010)
Under the rules of the valid Constitution of the Republic of Hungary and the Act based on it (Act L of 2005) the dualist concept is applied to the relationship of international law and domestic law. With respect to that, an international obligation/international treaty becomes part of the Hungarian legal system only through its transformation, i.e. enactment into a (Hungarian) domestic legal source and publication (promulgation). Present study analyzes those anomalies, concerns and dilemmas, owing to which the viability of the present system is questioned. Mentioning a few examples: what are the consequences, if the Hungarian legislator does not fulfil its obligation to publication, it "comes to light" before the publication of an international treaty already ratified by the Republic of Hungary, that the act of publication contradicts the Constitution, the act of publication is of minor rank in hierarchy, than the already/still valid Hungarian law, etc. This study aims at gathering such and like problems.
Keywords: Társadalomtudományok; Jogtudomány